ANALISIS PELAKSANAAN PENGADAAN TANAH UNTUK KEPENTINGAN UMUM DI KABUPATEN KONAWE KEPULAUAN - Sulsalman Moita (Universitas Halu Oleo, 2020)
The purpose of this study is to find out and study the analysis of the implementation of land acquisition for public use in Konawe Kepulauan Regency. The method in this research is descriptive qualitative with a case study approach. Research locus in Langara City, with research informants namely parties involved in land acquisition. Data collection is done by in-depth interview techniques, observations, and document studies, while data analysis techniques are done qualitatively and quantitatively. The results of the study show that: analysis of the implementation of land acquisition for the construction of public facilities in Konawe Kepulauan Regency uses eight stages of procedures, where at each stage the authority of the regional government working together National Land Agency is quite dominant in policy making, such as location determination, socialization, land measurement, land survey, announcements the results of land survey and compensation. Whereas the community or landowner is the party that has suffered a lot from land acquisition policies, due to inadequate types of compensation, low compensation, and delays in fulfilling the rights of landowners. Other findings also indicate the occurrence of a conflict of interest between the land owner and the land acquisition (local government) related to the status and claim on the land so that it impacts on the legality of the land, whether including land owned or state land